VERBAL INFLUENCE IN THE INFORMATION WARS: IDENTIFYING THE SUGGESTIVE PATTERNS - А. В. Ковалевська (Записки з українського мовознавства, 2017)
The article deals with researching the information warfare (IW) phenomenon in the paradigm of such brand new complex sciences as Neuro-Linguistic Programming (NLP), Suggestive Linguistics, Theory of Lies, and represents the development of the author’s IW classification based on identifying the repeated influential linguistic patterns, and the specific markers of the influential techniques as described in NLP’s Milton model and P. Ekman’s classification of lies. In the research, each of the offered information war types is characterized as a special communicative pattern with its own verbal and semantic peculiarities. Revealing these patterns would allow not only to describe the characteristics of information wars as the linguistically influential phenomenon of the modern information society in detail, but also to subsequently develop mechanisms for identifying the IW processes, widespread both in Ukrainian and world mass media, which would help minimize IWs’ harmful influence.